Reviews. (1st March 2015) - Carrier, David; Vigneron, Frank
'Mao's Golden Mangoes and the Cultural Revolution', China Institute, New York, 18 September 2014-26 April 2015Zheng Chongbin. Impulse, Matter, Form, Br itta Er ickson (ed.) (2014), Beijing: Ink Studio, 123 pp., ISBN: 978-0-615-86453-2 (US45)